An Analysis of Islamic Law in the Perspective of Contemporary Fiqh - Munawir Harahap (ISNU Sumatera Utara, 2024)
The rapid development of the times has given rise to various contemporary issues that were previously unimaginable. This demands a dynamic and contextual interpretation and application of Islamic law to the current context. In response to these challenges, contemporary fiqh emerges as a discipline that actively interprets and applies Islamic law in the modern context.This study aims to analyze Islamic law in the perspective of contemporary fiqh through a library research method. Library research is conducted by collecting, analyzing, and synthesizing various related literature, such as classical fiqh books, works of contemporary scholars, scientific journals, and other reliable sources.This study is expected to contribute to an understanding of the important role of contemporary fiqh in responding to various contemporary issues and maintaining the relevance of Islamic law in the modern era. In addition, this study is expected to be a reference for academics, Islamic law practitioners, and the general public in understanding Islamic law more comprehensively and contextually.